LITERATURE REVIEW: EFEK MIRROR THERAPY TERHADAP PENINGKATAN FUNGSI MOTORIK PADA PENDERITA POST STROKE - Rizky Yulian Candra (2021)
Stroke is a disorder that occurs caused cloged or outbreak of blood vessels in the brain resulting in impaired motor function, this requires an intervention to restore motor function motion, such as mirror therapy which aims to improve motor function in post-stroke patients. The purpose of this paper is to examine the effectiveness of mirror therapy on scientific articles that are reviewed. The research method used is literature review. The scientific articles used are research with the type of research study with titles that match the keywords in the 2016-2021 range. It has been found 5 scientific articles that are used in accordance with the paper criteria. the results that have been found with significant test and pre and post test with a value P < 0.005 and P < 0.001 in the group given mirror therapy. which means mirror therapy have an effect on improving motor function in post-stroke patients.